(untitled) - DiYanni, Robert (Boston, 2004)
This book presents 55 stories; 334 poems; 16 plays and offers the refreshing New Voices of authors whose writing has never before appeared in an introductory text, in addition to classic works, eight Authors in Context, and an engaging Transformations chapter
Keywords: Literature,Văn học